Coaching in hospitality - Breitenmoser, Kurt.; McCrae, Louise; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2011)
"The longevity of the hospitality industry is dependent on the quality of coaching given to today's trainees and apprentices. Yet many hospitality managers consider coaching a time-consuming and costly exercise. This program uses input from hospitality training experts and loads of real world footage and examples to shine a spotlight on coaching in a hospitality environment, and to explain key factors for effective coaching. We start by outlining the purpose and importance of coaching, followed by preparing for coaching. Next is an in-depth look at on-the-job coaching, followed by the all-important follow-up.We conclude by reinforcing the many benefits of coaching"--Container.
Director, Kurt Breitenmoser.
Voice over: Louise McCrae.
Keywords: Employees -- Coaching of; Hospitality industry -- Employees -- Training of